The Effect of Creative Thingking Ability and Basic Mathematics Ability Toward Students Problem Solving - Made Subawo (JME (Journal of Mathematics Education), 2022)
This research is an ex post facto research with a quantitative approach. The population in this study were all class VIII of SMP Negeri 2 Ladongi with a total of 73 students. Using total sampling technique so that a total sample of 73 students is obtained. Data collection techniques using tests. Data analysis using multiple regression analysis. The conclusions in this study are as follows: (1) Decryptively, students' mathematics creative thinking abilities are in the quite creative category, students' basic mathematics abilities are in the medium category, students' mathematics problem solving abilities are in the low category; (2) there is a significance influence of students' mathematics creative thinking skills on mathematics problem solving abilities with thitung > ttabel 8,81 >1,666 and sig < ? atau 0,001 < 0,05; (3) There is a significance positive effect on basic mathematics ability on mathematics problem solving ability with thitung > ttabel or 3,10 > 1,666 and sig < ? atau 0,004 < 0,05; (4) There is a significance positive influence on mathematics creative thinking skills and basic mathematics abilities on the mathematics problem solving abilities of class VIII students of SMP Negeri 2 Ladongi with FHitung = 65,71 or FTabel = 3,13 or FHitung ? FTabel and significance = 0.000 < ? = 0.05